Efficient lead Pb(II) removal with chemically modified Nostoc commune biomass - Ángeles Suazo, Julio Miguel (2022)
A new biosorbent based on Nostoc commune (NC) cyanobacteria, chemically modified with NaOH (NCM), has been prepared, characterized and tested as an effective biomass to remove Pb(II) in aqueous media. The adsorption capacity of NCM was determined to be qe = 384.6 mg g−1. It is higher than several other biosorbents reported in the literature. Structural and morphological characterization were performed by FTIR, SEM/EDX and point zero of charge pH (pHPZC) measurements. NCM biosorbent showed more porous surfaces than those NC with heterogeneous plates including functional adsorption groups such as OH, C = O, COO−, COH or NH. Optimal Pb(II) adsorption occurred at pH 4.5 and 5.5 with a biomass dose of 0.5 g L−1. The experimental data of the adsorption process were well fitted with the Freundlich-isotherm model and pseudo-2nd order kinetics, which indicated that Pb(II) adsorption was a chemisorption process on heterogeneous surfaces of NCM. According to the thermodynamic parameters, this process was exothermic (∆H0 < 0), feasible and spontaneous (∆G0 < 0). NCM can be regenerated and efficiently reused up to 4 times (%D > 92%). NCM was also tested to remove Pb (%R~98%) and Ca (%R~64%) from real wastewater.